Xena, warrior princess. Season one / Disc 1, 2 & 3 - MacDonald, Michael; Smith, Chloe; Stewart, R. J.; Schulian, John, 1945-; Tapert, Robert; Lawless, Lucy, 1968-; O'Connor, Renee; Campbell, Bruce, 1958-; LoDuca, Joseph; Renaissance Pictures (Firm); Anchor Bay Entertainment, Inc.; LC Purchase Collection (Library of Congress) (Troy, MI : Dist. by Anchor Bay Entertainment, 2003)
Xena, a mighty warrior and healer, once led a band of outlaws that terrorized all of Greece. She has come to regret the harm she caused and, with her companion Gabrielle, now travels the countryside seeking adventure and fighting the forces of evil.
Disc 1. Sins of the past ; Chariots of war ; Dreamworker ; Cradle of hope -- disc 2. The path not taken ; The reckoning ; The titans ; Prometheus -- disc 3. Death in chains ; Hooves and harlots ; The black wolf ; Beware Greeks bearing gifts
Originally produced as a Universal Television series broadcast in 1995-1996.
Irregular original packaging.
Accompanying CD-ROM includes special features.
Special features: director and actor bios, series trivia, Xena chronicles, season one photo gallery, Xena screensaver.
Lucy Lawless, Renee O'Connor, Bruce Campbell, Kevin Smith, Robert Trebor.
DVD; region 1; 5.1 surround sound.
Keywords: Xena, Warrior Princess (Fictitious character); Female friendship; Fantasy television programs; Fiction television programs; Television programs -- New Zealand; Action and adventure television programs -- New Zealand; Drama; Television programs